2007
DOI: 10.1017/s174217050700186x
|View full text |Cite
|
Sign up to set email alerts
|

Does use of draft animal power increase economic efficiency of smallholder farms in Kenya?

Abstract: Draft animal power (DAP) has been identified as an environmentally friendly technology that is based on renewable energy and encompasses integration of livestock and crop production systems. Draft animal technology provides farmers with a possibility to cheaply access and use manure from the draft animals and farm power needed to apply renewable practices for land intensification. Compared to motorized mechanization, DAP is viewed as an appropriate and affordable technology especially for small-scale farmers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In one case, a state-sponsored tractor hire scheme in Kenya failed largely because the farms were too small to make using a tractor economically viable. Most farmers were unable to afford the costs associated with purchasing, maintaining, and operating mechanized farm equipment (Guthiga et al, 2007). Agricultural development models using DAP, as modeled by Tillers International, are more likely to succeed by equipping farmers with skills and the ability to produce tools locally rather than machines that require maintenance and fuel.…”
Section: Downloaded By [University Of Western Ontario] At 21:51 03 Fementioning
confidence: 99%
See 2 more Smart Citations
“…In one case, a state-sponsored tractor hire scheme in Kenya failed largely because the farms were too small to make using a tractor economically viable. Most farmers were unable to afford the costs associated with purchasing, maintaining, and operating mechanized farm equipment (Guthiga et al, 2007). Agricultural development models using DAP, as modeled by Tillers International, are more likely to succeed by equipping farmers with skills and the ability to produce tools locally rather than machines that require maintenance and fuel.…”
Section: Downloaded By [University Of Western Ontario] At 21:51 03 Fementioning
confidence: 99%
“…As such, "DAP represents a major advance in terms of available power" (Sims et al, 2012, p. 813) and reduces the amount of time and labor devoted to tasks such as tilling the land or transporting goods. DAP allows farmers to work more efficiently and productively; Guthiga et al (2007) found that adopting DAP led to both increased yields and profits for maize farmers in Kenya.…”
Section: Downloaded By [University Of Western Ontario] At 21:51 03 Fementioning
confidence: 99%
See 1 more Smart Citation
“…La comptabilisation des effluents et de la traction animale en addition des produits alimentaires n'est toutefois pas un nonsens considérant l'objectif de sécurité alimentaire dans ces zones. En effet, compte tenu de l'accessibilité difficile aux fertilisants minéraux et à la mécanisation, ces deux éléments sont des composantes essentielles de la durabilité de ces systèmes, notamment en améliorant significativement la productivité des cultures (Williams 1997, Savadogo et al 1998, Guthiga et al 2007, Rufino et al 2007 et, par conséquent, en améliorant la fourniture alimentaire pour la famille ou les produits de rente.…”
Section: / Une Méthodologie à Améliorer A) Faciliter L'adaptation Desunclassified
“…However, there is currently a lack of knowledge about the extent to which the farm machine use substitutes draft animal use. Moreover, most of the studies mentioned previously have either analysed the association between draft animal use and agricultural production [2,14], or the impact of farm machine use on agricultural productivity [5,9,12,15]. The estimates may be biased if households are jointly making decisions to use draft animals and to use farm machines in their efforts to enhance agricultural production.…”
mentioning
confidence: 99%